Exploring the Intrinsic Elements of Tarbiyah Ash-Shibyan and Their Relevance to Islamic Religious Education - Mustaqim, Mustaqim; AR, Samsul; Tamam, Khoirit (Dzil Majaz: Journal of Arabic Literature, 2025)
The classical scholars of the Malay–Indonesian archipelago paid great attention to Islamic education, leaving behind numerous works that reflect the integration of literature and moral pedagogy. One such work is Tarbiyah Ash-Shibyan by Muhammad Habibullah Ibn Rois Ibrohim, a poetic text that outlines moral guidance for children in their relationships with parents, teachers, peers, and society. This study aims to analyze the intrinsic elements of Tarbiyah Ash-Shibyan and explore its relevance to Islamic Religious Education, particularly in shaping moral character and ethical awareness. Employing a qualitative library research method with a descriptive-analytical approach, this research examines the text’s thematic structure, language style, and pedagogical message. The findings reveal that Tarbiyah Ash-Shibyan combines aesthetic beauty with moral instruction, functioning not only as a literary work but also as a medium of character education. The poetic form enhances memorization and internalization of moral values, making it a valuable tool in Islamic education. This study contributes to understanding how classical Islamic literature can serve as an effective model for moral and character education in contemporary contexts